2019
DOI: 10.1111/acer.14132
|View full text |Cite
|
Sign up to set email alerts
|

“Can't Wait to Blackout Tonight”: An Analysis of the Motives to Drink to Blackout Expressed on Twitter

Abstract: Background: Alcohol-related blackouts are associated with a range of negative consequences and are common among social drinkers. Discussing alcohol use on social networking platforms (e.g., Twitter) is common and related to higher alcohol consumption levels. Due to the widespread nature of alcohol-related social networking posts and alcohol-related blackouts, we examined the content of alcoholrelated blackouts posts/"Tweets" on Twitter, with a focus on intentions to black out and specific motivations for black… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 46 publications
3
27
2
Order By: Relevance
“…Using the firehose allows us to describe the trends in how cannabis has historically been referenced in New Zealand, unlike other studies that have limited their analysis to the most influential tweeters, used only 1-10% of tweets or have limited analysis to a short period of time (e.g. 1 month or weekend) [15,17]. Additionally, while it was not our goal to predict the outcome of the referendum, our data provide an example of how data of this nature can be collected, analysed and reported on in close to real time.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the firehose allows us to describe the trends in how cannabis has historically been referenced in New Zealand, unlike other studies that have limited their analysis to the most influential tweeters, used only 1-10% of tweets or have limited analysis to a short period of time (e.g. 1 month or weekend) [15,17]. Additionally, while it was not our goal to predict the outcome of the referendum, our data provide an example of how data of this nature can be collected, analysed and reported on in close to real time.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Twitter chatter may be particularly helpful for understanding views of the public leading up to the New Zealand cannabis referendum because of how common substance use posts are [15][16][17][18]. Indeed, a recent study in the USA found that around 2% of tweets written included a reference to alcohol [19] and 7.7 million English language cannabis-related tweets were written in 1 month in 2014 [17].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, previous research using tweets to track alcohol use patterns indicated that 2% of all tweets reference alcohol consumption [14]. Moreover, research suggests that social media users discuss alcoholinduced blackouts on Twitter [15,16]. Therefore, using Twitter to track alcohol-induced blackouts during the COVID-19 'stay at home' and 'shelter in place' orders, allows for the examination of real-time data in a naturalistic setting.…”
Section: Introductionmentioning
confidence: 99%
“…Monitoring Twitter, specifically for references to alcohol‐related blackouts, could provide information about how the pandemic impacted risky drinking. Given that some people tweet about desiring to blackout [16], it might also provide an early warning system regarding additional factors straining the health‐care system. Moreover, it provides data beyond self‐report surveys by examining expressions of cognition and behaviour that are not prompted by researchers.…”
Section: Introductionmentioning
confidence: 99%
“…Social networking sites are universal, with 5.8 million Australians using Twitter and 110 000 using Reddit each month 2 . Given that a number of these posts are publicly available, they can be used to answer research questions and track health behaviours, 3‐5 and may be an informative source of feedback on health guidelines during public consultation 6 …”
mentioning
confidence: 99%